Promotion signals, age and education - Michael L. Bognanno; Eduardo Melero (Institute for the Study of Labor (IZA), 2012)
This paper examines whether more informative job promotions carry larger wage increases. In job assignment models with asymmetric information, unexpected promotions send a signal to the external labor market to revise upward their assessment of a worker's ability. The employing firm must then increase wages to prevent the worker from being bid away. Less educated workers are assumed to come from a group with lower average ability. Their promotion is hypothesized to signal a larger positive assessment of their ability than for more highly educated workers for whom promotion is expected. Promotions for younger workers, with less known about their abilities, should also result in strong signaling effects. We find results in accordance with our hypotheses regarding the effect of both age and education on the gains to promotion. However, the statistical significance of the estimates hinges on the promotion definition. Younger workers receive statistically significantly higher wage increases upon promotion only when promotion is defined by the attainment of managerial responsibilities not previously held. Less educated workers obtain statistically significantly larger wage increases upon promotion at a weak level of significance (10%) across definitions of promotion but at a high level of significance (5%) only when the subjective definition of promotion is used. We interpret the sensitivity to the definition of promotion to suggest that promotions may be heterogeneous in the information they reveal about the employee in way that depends on the characteristics of the employee.
urn:nbn:de:101:1-201207125644
Keywords: J3; 330; promotion; signaling; internal labor markets; Erwerbsverlauf; Lohn; Interner Arbeitsmarkt; Altersgruppe; Qualifikation; Bildungsniveau; Schätzung; Großbritannien